Peranan Lembaga Wanita Hindu Dharma Indonesia (WHDI) DKI Jakarta Dalam Pemberdayaan Perempuan Hindu - Nanda Rizka Saputri (Jurnal PASUPATI, 2019)
This research intend to explain task and function from Wanita Hindu Dharma Indonesia (WHDI) DKI Jakarta organization, to know the WHDI organization programs of activities and review performance the role of WHDI organization empower the Hindus woman in DKI Jakarta Province. The type of this research use descriptive method from qualitative analysis. The technique to collect data with data reduction, display, verification and conclusion. From this research, researcher interview 4 informaces namely 3 WHDI organization managements and 1 woman activist from Sarinah. The result of this research show the WHDI organization program of activities rate have run of their role well in empowerment the Hindus womans in DKI Jakarta although only from particular field has been implemented and support factors to participation of Hindus woman to follow program empowerment of activities WHDI organization in DKI Jakarta including available support from religion figure and society figure in socialization process and implementation activities program. Written the short history how WHDI DKI Jakarta was built in the past as the references how the program and activity made.